Good Governance, Kompetensi SDM, Budaya Organisasi dan Kinerja Pengelolaan Dana Desa - Ariani, Ayu; Gayatri, Gayatri (E-Jurnal Akuntansi, 2021)
The high demand for accountability in the management of village funds which must be the top priority of the village government is a phenomenon that usually occurs within the scope of village government. Village government does not only demand capability and professionalism but for now emphasizes the realization of a government that is free from corruption, collusion and nepotism (KKN). The purpose of this study was to determine the effect of good governance, human resource competence, and organizational culture on the performance of village fund management in Mengwi District. This study used 75 samples. In collecting data, researchers used a questionnaire method that was distributed directly to respondents. The data analysis technique used is Multiple Linear Regression Analysis. The results showed that Good governance, Human Resource Competence, and Organizational Culture had a significant positive effect on the Performance of Village Fund Management in Mengwi District. Keywords: Good Governance; Competency; Culture; Performance.